Seismic Damage Analysis of Large-Span Tied-Arch Bridge with Concrete-Filled Steel Tubes Subjected to Near-Fault Ground Motion - Yingzhi Xia; Jiawei Liu; Hui Li; Guoping Hu (Geofluids)
In this study, the damage mechanism due to near-fault ground motions on large-span arch bridges with concrete-filled steel tubes was investigated based on a case study. A tied-arch bridge with concrete-filled steel tubes with a span of 460 m has been examined using the numerical simulation method. The performance of the bridge was analyzed in terms of displacement, overall response, internal force changes, and damage probability considering the various near-fault and non-near-fault ground motions when imposing load onto the bridge. Then, the relationship between the bridge damage and the design parameters of ground motion intensities, near-fault velocity pulse, and excitation angle was obtained. The results indicated that the probability of damage caused by near-fault earthquakes is significantly higher than that by non-near-fault ground motions, and velocity pulses may cause more severe damages to certain components of the bridge during lower-intensity ground motions at certain excitation angles. And the damage furtherly resulted in the weakening of the bridge structure and decrease in its load-carrying capacity. Therefore, the near-fault ground motion should be fully considered in the design of large-span arch bridges with concrete-filled steel tubes in practical engineering.